Inspection of intermodular connection locations for multistory modular buildings - Moon, Jae Sang; Seo, Wonseok; Ahn, Hyeunguk; Kim, Jinyoung (Measurement and Control (United Kingdom), 2024)
Modular construction is a method of construction that involves prefabricating modular indoor spaces in a factory and then assembling them at the construction site. However, dimensional errors made during production in the modular manufacturing factory may hinder assembly at the construction site and delay the entire construction process. In particular, as the quality of intermodular connections determines the structural performance and serviceability of the entire modular building, meticulous quality control is required for the connections. In this study, a method is developed for inspection of the intermodular connection locations to meet the requirements of being accurate, inexpensive, easy-to-use, rapid, and operable by a single person, and then tested in a modular factory. The proposed inspection method consists of three parts: (a) a laser meter mounted on a gimbal, (b) target reflectors based on the tumbling doll principle, and (c) a mobile device as a remote control and for data storage, data post-processing, and visualization of results. The proposed inspection process was tested on a modular unit that had been manufactured at a modular factory; the proposed method outperformed the conventional method in terms of accuracy, inspection time, and work safety. The proposed inspection method allows the accurate and rapid inspection of locations of intermodular connection holes and, thus, its use in modular factories is likely to improve the economics and efficiency of modular construction.
Keywords: Construction sites; Dimensional errors; Gimbal; Indoor space; Inspection methods; Intermodular connection hole; Laser meter; Methods of constructions; Modular buildings; Modulars; gimbal; inspection method; intermodular connection hole; laser meter; Modular construction